Factors Related to Soil Transmitted Helminth Infection in Vegetable Farmers - Ririh Jatmi Wikandari; Lilik Setyowatiningsih; Masrifan Djamil; Surati Surati; Fitriani Kahar (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2021)
Soil Transmitted Helminth (STH) infection can occur at all ages, from children to the elderly. Farmers are at risk of contracting STH infection because of their daily work which is in direct contact with the soil. The risk of STH infection is due to poor personal hygiene and environmental sanitation. The study aims to determine observe the factors associated with STH infection in vegetable farmers, using a cross-sectional approach. The research subjects were vegetable farmers in Batur Wetan Hamlet, Getasan, Semarang Regency. Data were collected using a questionnaire to determine the personal hygiene and sanitation hygiene of farmers when working in the garden. Worm identification used (reference,) based on the worm performance using the floating method. Worm identification were done by examining the stool using the floating method. The results of the study were processed using SPSS version 20. Data analysis using Chi-Square (α = 5%), found 3 positive study subjects infected with STH, consisting of 1 egg of Ascaris lubricoides and 2 eggs of Trichuris trichiura. Positive STH respondents, have a washing by water and soap habits before eating and defecating, without wearing gloves. There was a relationship between hand washing by water and soap habits before eating to worm infection, but no relationship between this habit after defecating and no wearing gloves to worm infection. Vegetable farmers are advised to change the daily habits and maintain personal hygiene after working. use personal protective equipment when working and maintain personal hygiene.